AGRICULTURE IN THE SOUTHWESTERN REGION OF BULGARIA AND ITS IMPACT ON RURAL DEVELOPMENT - Miteva, Albena; Doitchinova, Julia (Economics of Agriculture, 2022)
The aim of the study is to analyze and evaluate the development of agriculture and its impact on rural areas in the Southwest Region. To assess the importance of agriculture in the region and trends in its development, a mixed methodology is used, combining quantitative and qualitative methods. The results and conclusions are based on statistical information from the Ministry of Agriculture and the National Statistical Institute, as well as on expert assessment of specialists from the regional offices of the State Fund “Agriculture” and the National Agricultural Advisory System in the four rural areas. The changes and features of the formed model of agriculture in the Southwest region have been analyzed and evaluated. The emphasis is placed on the processes for reducing the number of small family farms, in their size, on the processes of diversification of activities, on the greening of economic activity, etc.